KEPASTIAN HUKUM PEMBAGIAN HARTA BERSAMA AKIBAT HILANGNYA SALAH SATU PASANGAN DALAM PERKAWINAN (Studi Komparatif Berdasarkan Hukum Perdata dan Kompilasi Hukum Islam) - Hamdani Hamdani (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2019)
The loss of a husband and wife certainly has legal consequences that must be sought for certainty in terms of marital status, the sharing of shared assets, or the distribution of inheritance. There is a significant debate between the Civil Code and the Compilation of Islamic Law related to how long it takes to determine the loss of a person and the distribution of shared property if the missing person is a husband or wife.This research is a descriptive analysis that leads to normative legal research, with a research approach to legal systematics. Data collection tool is obtained from secondary data, namely by means of literature study (library research). The data obtained were then analyzed using qualitative analysis. Based on the results of the study found that the determination of the legal status of missing persons based on the Civil Code in Article 467 of the Civil Code determines that someone who has left his residence within a period of 5 (five) years, or has passed 5 (five) years since the last clear clarity news about the condition of the person without authorizing to represent civil affairs and interests with the person to the Court to be summoned to appear before the court to ascertain their existence and fate and whereas according to Government Regulation Number 9 of 1975 Article 19 point (b) it is stated